2008
DOI: 10.1111/j.1570-7458.2008.00732.x
|View full text |Cite
|
Sign up to set email alerts
|

Romaine lettuce latex deters feeding of banded cucumber beetle: a vehicle for deployment of biochemical defenses

Abstract: Latex is widely found among plant species and is known to play a defensive role against certain herbivores. Two romaine lettuce, Lactuca sativa L. (Asteraceae) cultivars, ‘Valmaine’ (resistant) and ‘Tall Guzmaine’ (susceptible), were selected to study the potential of latex as a defense mechanism against the banded cucumber beetle, Diabrotica balteata LeConte (Coleoptera: Chrysomelidae). Latex from Valmaine strongly inhibited feeding of adult D. balteata compared to latex from Tall Guzmaine when applied to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 46 publications
(66 reference statements)
0
15
0
Order By: Relevance
“…The latex of lettuce ( Lactuca sativa ), of the common dandelion ( T . officinale ) and of many other plant species contains further defence‐associated secondary metabolites and proteins (Sethi et al ., ; Konno, ; Huber et al ., ) suggesting that TbSRPPs may participate in natural rubber and/or latex defence machinery. Summarizing the knowledge gained about SRPP localization, regulation and function from previous reports (Hillebrand et al ., ; Fricke et al ., ), we hypothesized that TbSRPP1 could be the first isoform to respond to stress, followed by TbSRPP3, whereas TbSRPP4 and TbSRPP5 are mainly responsible for rubber particle integrity.…”
Section: Discussionmentioning
confidence: 99%
“…The latex of lettuce ( Lactuca sativa ), of the common dandelion ( T . officinale ) and of many other plant species contains further defence‐associated secondary metabolites and proteins (Sethi et al ., ; Konno, ; Huber et al ., ) suggesting that TbSRPPs may participate in natural rubber and/or latex defence machinery. Summarizing the knowledge gained about SRPP localization, regulation and function from previous reports (Hillebrand et al ., ; Fricke et al ., ), we hypothesized that TbSRPP1 could be the first isoform to respond to stress, followed by TbSRPP3, whereas TbSRPP4 and TbSRPP5 are mainly responsible for rubber particle integrity.…”
Section: Discussionmentioning
confidence: 99%
“…The use of plantbased compounds is one of the alternatives to control insect pests. Many studies have been conducted on the repellent and antifeedant properties of plant extracts against insect pests (e.g., Erler et al, 2006;Tapia et al, 2007;Gahukar, 2008;Sethi et al, 2008;Napal et al, 2009). Many studies have been conducted on the repellent and antifeedant properties of plant extracts against insect pests (e.g., Erler et al, 2006;Tapia et al, 2007;Gahukar, 2008;Sethi et al, 2008;Napal et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Through their repellent and antifeedant effects, they can manipulate insect behavior and protect host plants from phytophagous insect pests (Isman, 2008). Many studies have been conducted on the repellent and antifeedant properties of plant extracts against insect pests (e.g., Erler et al, 2006;Tapia et al, 2007;Gahukar, 2008;Sethi et al, 2008;Napal et al, 2009). However, considering the vast array of plant resources, more studies need to be undertaken to come up with effective plant-based insecticides to control phytophagous insect pests.…”
Section: Introductionmentioning
confidence: 99%
“…Host plant resistance in lettuce to BCB and SL has been identified, as Nuessly and Nagata (1994) reported that 'Valmaine', a romaine lettuce cultivar, had a high level of resistance to SL. This cultivar was later found to be resistant to BCB (Huang et al, 2002;Sethi et al, 2008) and two lepidopterans, Trichoplusia ni and Spodoptera exigua (Sethi et al, 2006). 'Valmaine' is an obsolete cultivar that was used in lettuce production in 1970s and then used as a parent for crosses for development of romaine cultivars in the University of Florida (UF) lettuce breeding program (Guzman, 1986;Guzman and Zitter, 1983).…”
mentioning
confidence: 99%